Band gap modulation of SrTiO3 upon CO2 adsorption. Issue 25 (16th June 2017) - Sopiha, Kostiantyn V.; Malyi, Oleksandr I.; Persson, Clas; Wu, Ping
Abstract : In this study, we demonstrate that surface states at the SrTiO3 (001) surfaces can be suppressed by CO2 adsorption, opening new perspectives for sensing applications. Abstract : Herein, CO2 chemisorption on SrTiO3 (001) surfaces is studied using ab initio calculations to establish new chemical sensing mechanisms. It was found that CO2 adsorption opens the band gap of the material. However, the mechanisms are different: the CO2 adsorption on the TiO2 -terminated surface neutralizes the surface states at the valence band (VB) maximum, whereas for the SrO-terminated surface it suppresses the conduction band (CB) minimum. For the TiO2 -terminated surface, the effect is explained by the passivation of dangling bonds, whereas for the SrO-terminated surface, the suppression is caused by surface relaxation. Modulation of the VB states implies a more direct change in charge distribution, and thus, the induced change in the band gap is more prominent at the TiO2 termination. Further, it has been shown that both CO2 adsorption energy and surface band gap are strongly dependent on CO2 coverage, suggesting that the observed effect can be utilized in sensing applications for a wide range of CO2 concentrations.